Nutrition Assessment in Student-Run Clinics Serving Hispanic/Latinx Patients - Katherine Lilja; Teal Walters; Megan Dennis Baumler; Ambria Crusan (Journal of Student-Run Clinics, 2022)
Background: The patients of student-run clinics, especially Hispanic/Latinx patients, are at a disproportionately high risk for chronic disease due to the negative impacts of the social determinants of health, including barriers to obtaining healthcare, ranging from lack of financial resources to fear of deportation. Nutrition services are pivotal in providing effective, holistic healthcare for this patient population seeking care at student-run clinics. The purpose of this review is to examine how nutrition assessment is conducted at student-run clinics and to determine if the nutrition assessments are culturally tailored.Methods: Three scientific databases were searched using keywords focused on the concept of nutrition assessment in student-run clinics serving the Hispanic/Latinx population. The articles generated were reviewed by 4 independent reviewers to determine key elements related to nutrition assessment and/or nutrition services provided in student-run, free, or community clinics, with attention to addressing social and cultural barriers addressed by the clinic.Results: A search of the literature related to nutrition services at student-run clinics yielded 3 results for nutrition assessment of the Hispanic/Latinx population in student-run, free, or community clinics. Several articles presented research on health behavioral counseling and food insecurity screening, but few studies were conducted specifically on nutrition assessment, especially for the Hispanic/Latinx population.Conclusions: The current assessment tools have widespread use in nutrition assessment; however, they are insufficient for the distinctive characteristics of the Hispanic or Latinx population being served in a student-run clinic. Including dietetics students into a student-run clinic, if plausible, and/or a culturally sensitive guided nutrition assessment tool for students would be of benefit to adequately address the relevant social determinants of health in the nutrition assessment of patients at student-run clinics.